2014
DOI: 10.1021/la404513h
|View full text |Cite
|
Sign up to set email alerts
|

The Elasticity of Soap Bubbles Containing Wormlike Micelles

Abstract: Slow-motion imaging of the rupture of soap bubbles generally shows the edges of liquid films retracting at a constant speed (known as the Taylor−Culick velocity). Here we investigate soap bubbles formed from simple solutions of a cationic surfactant (cetyltrimethylammonium bromide -CTAB) and sodium salicylate. The interaction of salicylate ions with CTAB leads to the formation of wormlike micelles (WLM), which yield a viscoelastic behavior to the liquid film of the bubble. We demonstrate that these elastic bub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Notably, Debrégeas et al [187] have shown that during rupture, buckling instabilities can occur on the surface of bubbles in polymer melts. Sabadini et al, [186] on the other hand, have interestingly reported a complete absence of a rim (the tip of the expanding hole where liquid accumulates) in bubbles rupturing in viscoelastic wormlike micellar solutions. The reason for this is currently unknown.…”
Section: Bubble Rupture Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Debrégeas et al [187] have shown that during rupture, buckling instabilities can occur on the surface of bubbles in polymer melts. Sabadini et al, [186] on the other hand, have interestingly reported a complete absence of a rim (the tip of the expanding hole where liquid accumulates) in bubbles rupturing in viscoelastic wormlike micellar solutions. The reason for this is currently unknown.…”
Section: Bubble Rupture Dynamicsmentioning
confidence: 99%
“…Firstly, recent studies have revealed the influence of bulk elasticity in the hole opening kinetics of bubbles in a number of systems such as Boger fluids [185], wormlike micelles [186], and polymer melts [187]. In all cases, at short times, bulk elasticity was revealed to increase the hole opening velocity by as much as 10 4 times as compared to a Newtonian fluid of similar viscosity.…”
Section: Bubble Rupture Dynamicsmentioning
confidence: 99%
“…These thickness measurements are consistent with a highly efficient localized Marangoni-driven thinning (T cap < T needle ) or thickening (T cap > T needle ) the cap. It should be noted how such needle localized perturbations affect the measurement of thickness h. Hence, care is needed when interpreting the relationship between the thickness of a film and its rupturing speed when the film is pierced using surface-active perturbations such as heat (Petit, Le Merrer & Biance 2015) or ethanol (Sabadini, Ungarato & Miranda 2014). For h ∼ 0.5-1 µm, the bubbles are thin enough that even less efficient mechanisms such as non-Marangoni-driven intrinsic intrusions (microbubbles or particles) can locally thin the film further for van der Waals forces and thermal fluctuations to be able to act.…”
Section: Localized Marangoni-driven Violent Deathmentioning
confidence: 99%
“…In any kind of liquid matrix, bubble walls may also break because of the presence of impurities like solid particles [20,21,22]. Bubble rupture, in turn, can open the way to liquid film retraction, whose extent and velocity depend on the interplay among inertial, surface, viscous, and elastic forces (in case the liquid phase is viscoelastic) [23,24,25,26,27]. The presence of solid objects suspended in the liquid matrix, then, can play a crucial role, since it can anticipate bubble rupture and affect the final morphology of the material [27].…”
Section: Introductionmentioning
confidence: 99%